Studi investigasi adsorpsi oksigen pada permukaan ZnO[111] - Listra Yehezkiel Ginting; Andam Deatama Refino; Lukman Nulhakim (Journal of Science and Applicative Technology, 2020)
The growth of ZnO is an interesting case in the study of functional materials. Adsorption of molecular oxygen onto the surface of Zn-terminated ZnO can be used as a sample case of ZnO crystal growth with its precursors. In this study, we want to see the tendency of molecular oxygen adsorption: whether it is adsorbed as a whole molecule or it is dissociated into the two constituting oxygen atoms before being adsorbed on oxygen adsorption sites for the growth of the crystal. Potential energy surface survey has been carried out on the three configuration of molecular oxygen based on their translational degree of freedom. The configuration of the oxygen molecule with O=O bond axis being normal to the surface tends to be adsorbed wholly as molecule with adsorption energy of 4.11 eV, while the configuration of bond perpendicular to the surface have the tendency to dissociate into individual atoms.